2020
DOI: 10.47162/rjme.61.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Severe traumatic brain injury (TBI) – a seven-year comparative study in a Department of Forensic Medicine

Abstract: Deaths caused by traumatic brain injury (TBI) increase in incidence every year worldwidely, mainly in developing countries. Thus, World Health Organization (WHO) estimates that in 2020, TBI will become the third main cause of death. In our study, we evaluated the deaths caused by TBI recorded within the Institute of Forensic Medicine of Craiova, Romania, between 2011 and 2017. Therefore, according to age, the cases were divided into two groups: people aged 0-18 years old (including 18 years old) and people age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Our study shows that brain changes in the case of severe TBI are complex, which requires special therapeutic measures to save the patient's life and recovery after neurological sequelae. Most of the studies in recent years showed the severity and complexity of TBI [73][74][75][76] and the need to continue investigations to identify the biological markers that can offer information on the severity of neurological lesions and the efficiency of therapeutic measures.…”
Section: Figure 6 -Ihc Changes In Cerebral Parenchyma In Patients Dec...mentioning
confidence: 99%
“…Our study shows that brain changes in the case of severe TBI are complex, which requires special therapeutic measures to save the patient's life and recovery after neurological sequelae. Most of the studies in recent years showed the severity and complexity of TBI [73][74][75][76] and the need to continue investigations to identify the biological markers that can offer information on the severity of neurological lesions and the efficiency of therapeutic measures.…”
Section: Figure 6 -Ihc Changes In Cerebral Parenchyma In Patients Dec...mentioning
confidence: 99%